Beyond disruption : innovate and achieve growth without displacing industries, companies, or jobs - Kim, W. Chan; Mauborgne, Renée (Boston, Massachusetts : Harvard Business Review Press, 2023)
"Disruption dominates innovation theory and practice. But disruption is destructive-displacing jobs, companies, and even entire industries. Are we missing better, and even bigger, opportunities to innovate and grow? With three decades of research, the number one global-bestselling authors of Blue Ocean Strategy W. Chan Kim and Renée Mauborgne reveal another way to innovate and grow-nondisruptive creation. Just as Blue Ocean Strategy redefined the essence of strategy as creating not competing, Beyond Disruption redefines and expands the existing view of innovation by introducing a new approach-nondisruptive creation-that is free from the destructive displacement that happens when innovators set out to disrupt. Kim and Mauborgne reveal the distinct advantages of nondisruptive creation to business and society, showing how this bold, new approach to innovation allows companies to grow while also being a force for good. With examples that cut across all sectors of the economy and a practical framework for guiding innovation efforts, this book shows: why nondisruptive creation matters to all of us and why it's about to become a lot more important in the future; how to create innovation strategies that trigger nondisruptive creation instead of disruption; how to identify and execute on nondisruptive opportunities; and how companies can more thoughtfully pursue their growth and innovation strategies in a way that better balances business and society. A practical guide for driving innovation and growth, the rich research behind the book coupled with its frame-breaking message make it the must-read book for the next generation of innovators who want to do well and do good"--
Innovation and Growth without Disruption -- The Economic and Social Impact of Nondisruptive Creation -- The Four Sources of Business Advantage -- The Rising Importance of Nondisruptive Creation -- The Three Paths to Market-Creating Innovation and Growth -- Lead with the Right Perspectives -- Identify a Nondisruptive Opportunity -- Find a Way to Unlock the Opportunity -- Realize the Opportunity -- Build a Better World Together.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Technological innovations; Success in business; Economic development; Business ethics; Disruptive technologies; Business ethics; Disruptive technologies; Economic development; Success in business; Technological innovations